Research on Power Quality Control Device with Super Capacitor and Active Power Filter and Its Control - LONG Lilan; AN Youbin; ZHANG Min; WU Mingshui (Kongzhi Yu Xinxi Jishu)
In order to increase the utilization rate of power quality control devices in micro-grid, a combined device based on super capacitor and active power filter was proposed by using the main circuit topological similarity and functional complementarity between super capacitor energy storage system and active power filter. This paper analyzes the structure characteristics and combination principle of the combined device, introduces the control strategies of bidirectional DC/DC module and DC/AC module of the combined device, and gives the switching logic of the combined device under two working modes of power regulation and harmonic control. The simulation results show that the device can perform the functions of power regulation, reactive compensation and harmonic control respectively according to the requirements, and verify the rationality and effectiveness of the combined device.